2019
DOI: 10.1017/ice.2019.5
|View full text |Cite
|
Sign up to set email alerts
|

ESBL-colonization at ICU admission: impact on subsequent infection, carbapenem-consumption, and outcome

Abstract: Objective:To determine whether colonization with extended-spectrum β-lactamase–producing Enterobacteriaceae (ESBL-PE) predicts the risk for subsequent infection and impacts carbapenem-consumption and outcome in intensive care unit (ICU) patients.Design:Prospective cohort study.Setting:The 2 ICUs in the University Hospital Basel in Switzerland.Patients:All patients admitted to the 2 ICUs providing mechanical ventilation and an expected ICU stay >48 hours.Methods:Patients were routinely screened for ESBL-PE c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 37 publications
(39 reference statements)
2
35
1
6
Order By: Relevance
“…Data from targeted admission screenings in Switzerland are comparable to numbers in Germany, where similar carriage rates among patients transferred from abroad for resistant Gram-negatives (13% vs. 14-17% in our review) and for MRSA (4% vs. 1-4% in our review) were found [6]. ESBL-prevalence from universal admission screening was 8% in a study included in our review, which is comparable to the 10% prevalence found in a German study [9,59]. One of the most urgent antibiotic resistant threats, coming along with increased morbidity and mortality in infected patients, are CPE [60].…”
Section: Discussionsupporting
confidence: 84%
“…Data from targeted admission screenings in Switzerland are comparable to numbers in Germany, where similar carriage rates among patients transferred from abroad for resistant Gram-negatives (13% vs. 14-17% in our review) and for MRSA (4% vs. 1-4% in our review) were found [6]. ESBL-prevalence from universal admission screening was 8% in a study included in our review, which is comparable to the 10% prevalence found in a German study [9,59]. One of the most urgent antibiotic resistant threats, coming along with increased morbidity and mortality in infected patients, are CPE [60].…”
Section: Discussionsupporting
confidence: 84%
“…in Enterobacteriaceae infections has looked at either high risk settings such as the ICU [23,24] or targeted specific populations such as bacteraemic patients [11,13,25] or cancer patients [14]. Few studies have investigated the mortality associated with 3GCR-EB infections in broader acute-care settings [1,12,13].…”
Section: Existing Research On the Clinical Impact Of Third-generationmentioning
confidence: 99%
“…Con eso, se enfatiza la importancia del rastreo de esos pacientes y ejecución oportuna de medidas de prevención, resultante de la identificación de colonizaciones multirresistentes en la comunidad, o sea, el paciente pude tanto ser colonizado en el ambiente hospitalario, como venir ya colonizado del ámbito comunitario (10)(11)(12) .…”
Section: Introductionunclassified